SCHOOL HEALTH PROGRAM AS AN EDUCATIONAL FACILITY IN INCREASING KNOWLEDGE ABOUT DENTAL AND ORAL HEALTH AT BUNGA BANGSA ELEMENTARY SCHOOL - Elizabeth Pranoto, Amelia; Fauziah, Yessy Andriani; Rahardjo, Pambudi; Agustia, Lita; Budi Teguh, Paulus; Santoso, Budi; Sularsih, Sularsih; Prananingrum, Widyasri; Ayu R, Dyah; Tsurayya, Nur; Widowati, Kharinna; Hadinata, Yongki (LPPM Univ. Ibn Khaldun Bogor, 2023)
Dental and oral health in Indonesia is still a health problem that requires attention. To address dental and oral health problems in Indonesia, particularly in school-age and adult groups, it is necessary to carry out promotive-preventive activities by inviting local universities and business entities that focus on dental and oral health. The most common dental and oral diseases are caries and periodontal disease. One of the strategies of the Ministry of Health of the Republic of Indonesia in reducing the number of dental caries sufferers is by declaring the